2016
DOI: 10.1098/rsos.160229
|View full text |Cite
|
Sign up to set email alerts
|

Depth and substratum differentiations among coexisting herbivorous cichlids in Lake Tanganyika

Abstract: Cichlid fish in Lake Tanganyika represent a system of adaptive radiation in which eight ancestral lineages have diversified into hundreds of species through adaptation to various niches. However, Tanganyikan cichlids have been thought to be oversaturated, that is, the species number exceeds the number of niches and ecologically equivalent and competitively even species coexist. However, recent studies have shed light on niche segregation on a finer scale among apparently equivalent species. We observed depth a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 58 publications
0
1
0
1
Order By: Relevance
“…While consumer effects on prey are well known, the role of consumer diversity in affecting community structure or ecosystems is not particularly well understood, although Burkepile and Hay (2008) demonstrated that herbivorous fish species richness is critical for preserving coral reefs. Herbivores also form an important component of communities in the African Great Lakes (Hata & Ochi, 2016), and their decline may have serious implications for these systems. For example, the decrease in diversity of Lake Victoria herbivorous haplochromine cichlids after the introduction of the Nile perch (Lates niloticus) could have led to trophic cascades in this ecosystem (Goldschmidt, Witte, & Wanink, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…While consumer effects on prey are well known, the role of consumer diversity in affecting community structure or ecosystems is not particularly well understood, although Burkepile and Hay (2008) demonstrated that herbivorous fish species richness is critical for preserving coral reefs. Herbivores also form an important component of communities in the African Great Lakes (Hata & Ochi, 2016), and their decline may have serious implications for these systems. For example, the decrease in diversity of Lake Victoria herbivorous haplochromine cichlids after the introduction of the Nile perch (Lates niloticus) could have led to trophic cascades in this ecosystem (Goldschmidt, Witte, & Wanink, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…En tanto que la segregación de nichos a través de la microdistribución diferencial de especies del género Haplocromis que se alimentan de "Aufwuchs" (perifiton), se asoció a la profundidad y otros parámetros topográficos en el lago Victoria (Seehausen y Bouton, 1997). También, en 15 especies herbívoras de 4 ecomorfos de alimentación en el lago Tangañica se detectó diferenciación en el uso de profundidad y sustrato entre las especies de un mismo ecomorfo (Hata y Ochi, 2016). Finalmente, en el Parque Nacional del Lago Malawi, la disposición de áreas de alimentación de la fauna que habitan los litorales rocosos sugiere segregación espacial, lo que potencialmente ha promovido la coexistencia entre las especies nativas e introducidas, ésto a más de 30 años de la introducción de estas últimas (Makocho y Stauffer, 2018).…”
Section: Ríounclassified